GC-MS and LC-MS analysis of Kakadu plum fruit extracts displaying inhibitory activity against microbial triggers of multiple sclerosis - Edwin Cock, Ian; Sirdaarta, Joseph; Matthews, Ben; White, Alan (Pharmacognosy Communications)
Multiple sclerosis is an autoimmune disease which can be triggered in genetic susceptible individuals by Acinetobacter spp. and Pseudomonas aeruginosa infections. Terminalia ferdinandiana (Kakadu plum) fruit has documented therapeutic properties as a general antiseptic agent. Extracts prepared from the leaves have also been shown to block several microbial triggers of autoimmune inflammatory diseases. This study examines the ability of Kakadu plum fruit extracts to inhibit some microbial triggers of multiple sclerosis. Methods: T. ferdinandiana fruit solvent extracts were investigated by disc diffusion assay against reference and clinical strains of A.baylyi and P. aeruginosa. Their MIC values were determined to quantify and compare their efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Active extracts were analysed by non-targeted HPLC-QTOF mass spectroscopy (with screening against 3 compound databases) and by GC-MS (with screening against 1 compound databases) for the identification and characterisation of individual components in crude plant extracts. Results: Methanolic, aqueous and ethyl acetate T. ferdinandiana leaf extracts displayed potent antibacterial activity in the disc diffusion assay against the bacterial triggers of multiple sclerosis (A.baylyi and P. aeruginosa). The methanol and ethyl acetate extracts had the most potent growth inhibitory activity, with MIC values less than 1000 µg/ ml against A. baylyi and P. aeruginosa (both reference and clinical strains). In comparison, the water extract was substantially less potent. Neither the chloroform nor hexane extracts inhibited the growth of any of the bacterial strains tested. All T. ferdinandiana fruit extracts were nontoxic in the Artemia fransiscana bioassay. Non-biased phytochemical analysis of the ethyl acetate extract revealed only low levels of the tannins gallic acid and chebulic acid and no other tannins. Conclusion: The low toxicity of the T. ferdinandiana fruit extracts and their potent inhibitory bioactivity against the bacterial triggers of multiple sclerosis indicates their potential as medicinal agents in the treatment and prevention of this disease. Phytochemical studies indicate that this activity is likely to be due to phytochemicals other than tannins.
Keywords: Antioxidant; Autoimmune inflammatory disease; Acinetobacter; Complementary and alternative therapies; Demyelinating disease; Kakadu plum; Pseudomonas aeruginosa; Terminalia ferdinandiana